A compact, wireless system for continuous monitoring of breast milk expressed during breastfeeding - Kim, Jihye; Oh, Seyong; Avila, Raudel; Shin, Hee-Sup; Banet, Matthew; Wicks, Jennifer; Banks, Anthony R.; Huang, Yonggang; Yoo, Jae-Young; Robinson, Daniel T.; Garfield, Craig F.; Rogers, John A. (Nature Biomedical Engineering, 2025)
Human milk is the ideal source of nutrition for infants. Most health organizations recommend direct breastfeeding from the first hour of life, extending throughout the first and second year. However, uncertainties regarding the volumes of milk ingested by the infant contribute to suboptimal rates of breastfeeding. Here we introduce a compact and unobtrusive device that gently interfaces to the breast via four electrodes and accurately measures expressed milk volume during breastfeeding through changes in the alternating current impedance. The data pass wirelessly to a smartphone continuously throughout each breastfeeding session for real-time graphical display. Comprehensive experimental and computational results establish the operating principles and guide engineering choices for optimized performance. Evaluations with 12 breastfeeding mothers over periods of as long as 17 weeks in the neonatal intensive care unit and in home settings illustrate the practical utility of this technology in addressing a critically important unmet need in maternal and neonatal care.
Keywords: Alternating current impedance; Breast milk; Breastfeeding; Continuous monitoring; Health organizations; Human milk; Real- time; Smart phones; Uncertainty; Wireless systems